Sustainable Development Management through Social Policy Instruments of the Eurasian Economic Union (Part 1) - G. G. Rubtsov; O. N. Misko (Евразийская интеграция: экономика, право, политика, 2023)
The article deals with the issue of the relevance of improving the social policy of the member countries of the Eurasian Economic Union through the mechanism of “transinstitutional cooperation” (TC) proposed by the authors of the work. It represents interstate integration within  the framework of the joint i mprovement of one or more public policy instruments (including social policy). The topic of the welfare state is discussed in the context of studying various areas of the socio-economic life of the EAEU members: the main political and legal document of the country — the Constitution, the national taxation system, quality of life indicators, the level of the shadow economy, the level of social inequality of different segments of the population, etc. The effectiveness of using various social policy instruments of the EAEU countries is compared in order to identify strengths and weaknesses, as well as the potential for their improvement within the framework of “institutional cooperation”.Aim. Taking into account the above, the purpose of the study was to analyze the patterns of development of the social policy of the Russian Federation, the republics of Belarus, Kazakhstan, Kyrgyzstan and Armenia, to consider their weaknesses and points of growth in order to identify the potential for strengthening integration ties based on the unification of social development tools.Task. To analyze various areas of social life of the EAEU member countries, identify similarities in development trends in order to create a basis for the formation of unified socio-economic transformations. To demonstrate social tools for the development of “transinstitutional interaction” within the boundaries of the Eurasian Economic Union.Methods. The following methods were used in the article: comparative analysis — to compare the effectiveness of social policy instruments in the EAEU countries, content analysis — when analyzing documents (constitutions) of EAEU members to identify signs that allow identifying the state as a social one, as well as formal-logical analysis — when clarifying the concepts “welfare state” and “institutional cooperation”.Results. Based on the results of the study, the principles of the “welfare state” are considered on the example of the member countries of the Eurasian economic integration, the economic essence of “institutional cooperation” is formulated and proposed for implementation, designed to develop interethnic relations both within the union and beyond. A comprehensive analysis of the instruments of social policy of all participants in the Eurasian integration has been carried out, and recommendations for improving the instruments have been proposed.Conclusion. The accumulating unresolved issues of an internal nature are forcing the leadership of the members of the Eurasian Economic Union to accelerate the processes of building an unconditional policy of the welfare state. The solution of such “social modernization” alone seems difficult to implement, in this regard, it is proposed to take the path of a collective solution of the social issue through a unidirectional, unified social policy built on the basis of “transinstitutional cooperation”. The conducted analysis of social policy instruments lays down the priorities in the development of mechanisms of “transinstitutional cooperation” by the members of the EAEU. The Republics of Kyrgyzstan, Armenia and Kazakhstan should focus on developing a unified strategy for youth and migration policies, the Russian Federation and the Republic of Belarus should focus on issues such as population aging, providing older citizens with pension savings, and encouraging the development of family and maternity institutions.